Entre o traço, a palavra e o riso: Henfil e a educação - Vaillões, Silvana de Araújo (2014)
This paper intends to verify the contribution of the work by the cartoonist and journalist Henfil for informal education. The Fradim magazines (issues 1-3) were used to show his contribuition as cartoonist.The literature survey included authors who analyzed Henfil s works, as Silva (2002 , 2004 , 2007) , Moraes (1997 ) , as well as in informal education: Gohn ( 2006, 2008 , 2010) , Bittencourt ( 1999); Fantin (2006 ) and Pacheco (2009 ). The use of comics as media for the contribution to the informal education included authors as Vergueiro (2009 ). It also aims to discuss the techniques used by the author, under the production of comics, their nuances and the scope that media has in contributing to the education and political awareness, especially emphasizing the period of repression and censorship where Henfil s work is inserted. Gubern & Gasca (2011 ) and Eisner (1989, 2005) contributed as authors for this analysis. The objective was to prioritize the upbringing of this artist s work; in order to do that , testimonies of people considered opinion leaders were collected , such as teachers , journalists , cartoonists and politicians who had contact with the work and felt influenced by his creation.Thus, we can say that the Henfil s work had also a social resonance on the them. By considering the Fradim magazines for analysis we seek to understand the author's work in a broad sense, since it appeared only in fragmented forms in other newspapers and magazines.The depictions of Henfil meant a way of opposition to the military regime , as well as his contributions to a broad new way of education and training : the one that comes through various media and from books; of what oneself is exposed to in everyday life.These contacts contribute to the educational training of people, however that does not happen in the formal educational spaces and are important for the perception of reality. Even that Henfil had used various languages and media to highlight his work, such as magazines, newspapers, television, theater and even film, the contribution offered by the comics may be considered unique, since it contributes to the formation of new readers, as well as the perception of a world that is inferred by the design, the graphic forms and language, which are not distanced from the critical conception of the subjects covered.